(untitled) - Knutson, Cody (Western Drought Cooodination Council, 1998)
This guide describes a practice step-by-step process for identifying actions that can be taken to reduce potential drought-related impacts before a drought occurs.
Keywords: Drought,Hạn hán; Agriculture,Nông nghiệp